Acute Effects of Substitution, and Addition, of Carbohydrates and Fat to Protein on Gastric Emptying, Blood Glucose, Gut Hormones, Appetite, and Energy Intake - Giezenaar C; Lange K; Hausken T; Jones KL; Horowitz M; Chapman I; Soenen S (MDPI (Basel, Switzerland))
Whey protein, when ingested on its own, load-dependently slows gastric emptying and stimulates gut hormone concentrations in healthy young men. The aim of this study was to determine the effects of substitution, and addition, of carbohydrate (dextrose) and fat (olive oil) to whey protein. In randomized, double-blind order, 13 healthy young men (age: 23 ± 1 years, body mass index: 24 ± 1 kg/m²) ingested a control drink (450 mL; ~2 kcal/'control') or iso-volumetric drinks containing protein/carbohydrate/fat: (i) 14 g/28 g/12.4 g (280 kcal/'M280'), (ii) 70 g/28 g/12.4 g (504kcal/'M504'), and (iii) 70 g/0 g/0 g (280 kcal/'P280'), on 4 separate study days. Gastric emptying (n = 11, 3D-ultrasonography), blood glucose, plasma insulin, ghrelin, cholecystokinin (CCK) and glucagon-like peptide-1 (GLP-1) concentrations (0⁻180 min), appetite (visual analogue scales), and ad-libitum buffet-meal energy intake (180⁻210 min) were determined. Substitution of protein with carbohydrate and fat was associated with faster gastric emptying (lower 50% emptying time (T50)), reduced suppression of ghrelin, and stimulation of GLP-1 (all P < 0.001); while the addition of carbohydrate and fat to protein did not affect gastric emptying or gut hormone responses significantly. Total energy intake (i.e., drink plus meal) was greater after all caloric drinks than control (P < 0.001). In conclusion, substitution of whey protein with dextrose and olive oil accelerated gastric emptying. Higher protein content of a mixed macronutrient drink increased gut hormone and insulin responses.
Keywords: whey protein; gastric emptying; gut hormones; blood glucose; appetite; 0908 Food Sciences; 1111 Nutrition and Dietetics